2020
DOI: 10.56059/jl4d.v7i3.433
|View full text |Cite
|
Sign up to set email alerts
|

Covid-19 School Closures in Low- and Middle-income Countries: Emergent Perspectives on the Role of Educational Technology

Katy Jordan

Abstract: The Covid-19 pandemic ushered in school closures at an unprecedented scale and prompted educational systems to find alternative teaching models at short notice. The role for educational technology in low- and middle-income countries (LMICs) has recently become the focus of much discussion. While prompted by the pandemic, the discussions surface latent issues in educational systems, and the perspectives and ambitions of organisations in relation to educational technology and LMICs. The influence of the discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…So here it was necessary for the author to identify recent examples with which he was already familiar. The recent pandemic saw a massive shift to using technology to support remote learning and as noted by Jordan (2020), support from carers, teachers, and communities was key. Makoe and Olcott (2021), however, point to evidence that university leadership was not adequately prepared for the shift while Mays and Aluko (2018) observe that in the move to distance education provision, the impact on students and teachers is often explored but not so often the impact on administrative support staff.…”
Section: Staff Rolesmentioning
confidence: 99%
“…So here it was necessary for the author to identify recent examples with which he was already familiar. The recent pandemic saw a massive shift to using technology to support remote learning and as noted by Jordan (2020), support from carers, teachers, and communities was key. Makoe and Olcott (2021), however, point to evidence that university leadership was not adequately prepared for the shift while Mays and Aluko (2018) observe that in the move to distance education provision, the impact on students and teachers is often explored but not so often the impact on administrative support staff.…”
Section: Staff Rolesmentioning
confidence: 99%
“…EdTech is often recognised as a means of improving children's learning outcomes in LMICs by delivering costeffective education, over distance, at scale and personalised to children's needs ⇡Jordan & Myers, 2022;⇡World Bank, 2020). However, evidence has also shown that the use of EdTech can lead to negative consequences, such as exacerbating socioeconomic divides, structural inequalities and gender disparities (⇡Crompton et al, 2021;⇡Jordan, 2020). To better understand how to achieve sustained and inclusive educational improvements, the use of EdTech needs to be studied using rigorous evidence and through gender, political economy, equity and intersectionality perspectives.…”
Section: Introductionmentioning
confidence: 99%